2014
DOI: 10.1016/j.celrep.2014.05.038
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Response to Virus Infection Is Independent of Small RNA Silencing

Abstract: Summary A successful cellular response to virus infection is essential for evolutionary survival. In plants, arthropods, and nematodes, cellular antiviral defenses rely on RNA interference (RNAi). Interestingly, the mammalian response to virus is predominantly orchestrated through interferon (IFN)-mediated induction of antiviral proteins. Despite the potency of the IFN system, it remains unclear whether mammals also have the capacity to employ antiviral RNAi. Here we investigate this by disabling either IFN, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 84 publications
1
82
0
Order By: Relevance
“…However, whether RNAi as originally defined-that is a posttranscriptional regulatory mechanism triggered by long double-stranded RNAs (dsRNAs) (3)-continues to function as an antiviral mechanism in mammalian cells has remained controversial. Most importantly, sequence analysis of small RNAs expressed in mammalian somatic cells infected by a wide range of viruses has failed to detect significant levels of virally derived siRNAs (4-7), whereas human and mouse cells lacking a functional Dicer protein, and hence incapable of producing either siRNAs or miRNAs, are generally very similar to WT cells in terms of their ability to support the replication of a wide range of RNA and DNA viruses (5,6), thus arguing against the existence of a protective RNAi response.…”
mentioning
confidence: 99%
“…However, whether RNAi as originally defined-that is a posttranscriptional regulatory mechanism triggered by long double-stranded RNAs (dsRNAs) (3)-continues to function as an antiviral mechanism in mammalian cells has remained controversial. Most importantly, sequence analysis of small RNAs expressed in mammalian somatic cells infected by a wide range of viruses has failed to detect significant levels of virally derived siRNAs (4-7), whereas human and mouse cells lacking a functional Dicer protein, and hence incapable of producing either siRNAs or miRNAs, are generally very similar to WT cells in terms of their ability to support the replication of a wide range of RNA and DNA viruses (5,6), thus arguing against the existence of a protective RNAi response.…”
mentioning
confidence: 99%
“…However, it is still debatable whether host miRNAs play antiviral roles in the physiological context of infection (43). For example, by global depletion or downregulation of host miRNAs, two recent studies show that the miRNA pathway does not counteract infection by a wide range of viruses in mammalian cells (82,83).…”
Section: Other Virus-host Mirna Interactionsmentioning
confidence: 99%
“…Backes et al used an alternative strategy to determine whether virus-derived small RNA is relevant to the antiviral response in mammalian hosts [41]. They engineered a vesicular stomatitis virus (VSV) carrying VP55, a vaccine virus protein that could inhibit mammalian RNAi by degrading small RNAs [41]. Their results demonstrated that carrying the VP55 protein does not benefit viral replication but enhances virus-induced IFN responses in mammalian hosts.…”
Section: Do Mammalian Rna Viruses Generate Functional Vsrnas?mentioning
confidence: 98%
“…These results also implied that mammalian cells mainly use IFNstimulated activity rather than RNAi-derived antivirus responses for preventing viral infection. Backes et al used an alternative strategy to determine whether virus-derived small RNA is relevant to the antiviral response in mammalian hosts [41]. They engineered a vesicular stomatitis virus (VSV) carrying VP55, a vaccine virus protein that could inhibit mammalian RNAi by degrading small RNAs [41].…”
Section: Do Mammalian Rna Viruses Generate Functional Vsrnas?mentioning
confidence: 99%